Parenting style and bullying and victimization: comparing foreign-born Asian, U.S.-born Asian, and White American adolescents - Hong, Jun Sung (Journal of family violence, 2021)
The purpose of the study is to explore whether the association between types of parenting styles and bullying and victimization are similar across White American, U.S.-born Asian, and foreign-born Asian adolescents. Authoritative parenting, which is characterized as being supportive and showing acceptance, is positively related to psychological well-being among White American youth. However, due to different cultural norms in parenting style, Asian parents whose parenting style appears to be controlling and lacking in warmth might differentially affect their children’s behavior and socialization in school. Sample was drawn from the 2009–2010 Health Behavior in School-Aged Children (HBSC) U.S. study. The most recent data were collected in the United States from 2009 to 2010. HBSC consisted of adolescents, aged 11, 13, and 15 years. The sample for the present study includes 1438 adolescents who identified as White American, U.S.-born Asian, or foreign-born Asian. Univariate analyses, bivariate analyses, and multiple linear regression analyses were conducted. The regression analysis was conducted separately for bullying victimization and perpetration across foreign-born Asians, U.S.-born Asians, and White Americans. Among foreign-born Asians, mother’s non-involvement was positively associated with bullying victimization. Among U.S.-born Asians, father’s non-involvement was found to be positively associated with bullying victimization, and authoritarian parenting was positively associated with perpetration. Among White Americans, both authoritative parenting and mother’s non-involvement were positively related to bullying perpetration. This study highlights the importance of understanding the association between types of parenting styles and adolescent bullying and victimization.